Strategi Pemasaran Digital dalam Meningkatkan Ekuitas Merek pada UMKM Sandangs - Pangestu, Ilham Asta; Nugroho, Rusdi Hidayat (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This journal discusses digital marketing strategies that can enhance the brand equity of micro, small, and medium enterprises (SMEs) on Sandangs platform. In this ever-evolving digital era, SMEs must adopt effective marketing strategies to expand their market reach and build customer trust in their brand. Digital marketing encompasses various elements, such as social media, websites, search engines, and online advertising campaigns. This journal presents various digital marketing strategies that are crucial for MSMEs and can be implemented to increase brand awareness. The aim of this journal is to deeply understand digital marketing strategies in enhancing brand equity for SMEs. With the adoption of effective, relevant strategies, SMEs can leverage the potential of the digital market to achieve greater success. This journal use a literature study research method through a descriptive qualitative analysis approach, where data is obtained through secondary data sources from previous research. Based on the literature study, effective and relevant digital marketing strategies can influence the brand equity of a specific product, particularly for SMEs. Keywords: Digital marketing, SME, brand equity, brand awareness, customer loyality